Conservation of Protein Kinase A Substrates in the Cnidarian Coral Spermatozoa Among Animals and Their Molecular Evolution - Morita, Masaya; Hanahara, Nozomi; Teramoto, Mariko M.; Tarigan, Ariyo Imanuel (Journal of molecular evolution, 2024)
The coral Acropora spp., known for its reef-building abilities, is a simultaneous hermaphroditic broadcast spawning species. Acropora spp. release gametes into seawater, activating sperm motility. This activation is mediated by adenylyl cyclase (AC) and protein kinase A (PKA). Notably, membrane-permeable cAMP (8-bromo-cAMP) promotes sperm motility activation of Acropora florida . While the signal transduction for PKA-dependent motility activation is highly conserved among animals, the downstream signaling of PKA remains unclear. In this study, we used mass spectrometry (MS) analyses to identify sperm proteins in the coral Acropora digitifera , as well as the serine/threonine residues of potential PKA substrates, and then, we investigated the conservation of these proteins from corals to vertebrates. We identified 148 sperm proteins of A. digitifera with typical PKA recognition motifs, namely RRXT and RRXS. We subsequently used ORTHOSCOPE to screen for orthologs encoding these 148 proteins from corals to vertebrates. Among the isolated orthologs, we identified positive selection in 48 protein-encoding genes from 18 Acropora spp. Subsequently, we compared the conservation rates of the PKA phosphorylation motif residues between the orthologs under positive and purifying selections. Notably, the serine residues of the orthologs under positive selection were more conserved. Therefore, adaptive evolution might have occurred in the orthologs of PKA substrate candidates from corals to vertebrates, accompanied by phosphorylation residue conservation. Collectively, our findings suggest that while PKA signal transduction, including substrates in sperm, may have been conserved, the substrates may have evolved to adapt to diverse fertilization conditions, such as synchronous broadcast spawning.